Pengenalan desain komunikasi visual dan animasi dalam dunia industri untuk pelajar Sekolah Menengah Atas - Dhika Yuan Yurisma; Ardian Jaya Prasetya (Universitas Pendidikan Indonesia (UPI), 2021)
In the development of the creative economy in Indonesia, visual communication design was able to contribute 579.3 billion Rupiah in 2016, but this only contributed 0.06% of the Gross Domestic Product (GDP) of all creative industry sub-sectors. Visual Communication Design is a branch of design science that studies communication concepts and creative expression, techniques and media by utilizing visual or visual elements to convey messages for specific purposes (information or persuasion purposes, namely influencing behavior). There are many things that can be learned in the world of DKV, one of which is animation. This service program aims to introduce high school and vocational students to the world of DKV and animation science in the industrial world. The material presented includes basic knowledge of DKV, animation and job opportunities. Socialization is carried out online using the zoom application. So that the participants who attended could cover all of Indonesia. At the end of the activity a questionnaire will be given to find out the participants' understanding, as much as 92% of participants understand the material presented. In the final conclusion, students have gained an understanding of the world of DKV and animation as one of their considerations in determining their further education.